Research and education form competing activity systems in externally funded doctoral education - Anders Sonesson; Lena Stenson; Gudrun Edgren (Taylor & Francis Group, 2023)
ABSTRACTSeveral authors have described how the formalization of recent decades has steered doctoral education towards structured curricula, more managerial control and new models for supervision. Largely absent from these accounts, however, is if and how doctoral education has been affected by the concurrent changes in research governance, in particular by the 'projectification' of research. For this study, we were interested in the convergence of educational formalization with research projectification around doctoral education in the context of highly competitive, externally funded research in medicine and health sciences in Sweden. Using Cultural-historical activity theory and constructing activity systems for education and research, respectively, we were able to identify several contradictions and tensions, both within and between systems, that were consequences of adaptations to the abovementioned formalization and research policy changes. The contradictions were manifested in the tying of doctoral students, and their education, to their supervisors' research projects, grants and future prospects, and in students being deprived of opportunities for learning and developing independence. Supervisors were torn between supervision and project management while doctoral students had to balance being students and project members. Our analysis provides a system level explanation to previously reported pedagogical and ethical challenges in STEM doctoral education.